Factors influencing prescribing behaviour of physicians in Greece and Cyprus: results from a questionnaire based survey - Fragoulakis Vasilis; Maniadakis Nikos; Pavlakis Andreas; Tsiantou Vasiliki; Theodorou Mamas; Pavi Elpida; Kyriopoulos John (BMC, 2009)
Abstract Background Over the past few decades, drug and overall healthcare expenditure have risen rapidly in most countries. The present study investigates the attitudes and the factors which influence physician prescribing decisions and practice in Greece and Cyprus. Methods A postal questionnaire was developed by researchers at the Department of Health Economics at the National School of Public Health in Greece, specifically for the purposes of the study. This was then administered to a sample of 1,463 physicians in Greece and 240 physicians in Cyprus, stratified by sex, specialty and geographic region. Results The response rate was 82.3% in Greece and 80.4% in Cyprus. There were similarities but also many differences between the countries. Clinical effectiveness is the most important factor considered in drug prescription choice in both countries. Greek physicians were significantly more likely to take additional criteria under consideration, such as the drug form and recommended daily dose and the individual patient preferences. The list of main sources of information for physicians includes: peer-reviewed medical journals, medical textbooks, proceedings of conferences and pharmaceutical sales representatives. Only half of prescribers considered the cost carried by their patients. The majority of doctors in both countries agreed that the effectiveness, safety and efficacy of generic drugs may not be excellent but it is acceptable. However, only Cypriot physicians actually prescribe them. Physicians believe that new drugs are not always better and their higher prices are not necessarily justified. Finally, doctors get information regarding adverse drug reactions primarily from the National Organisation for Medicines. However, it is notable that the majority of them do not inform the authorities on such reactions. Conclusion The present study highlights the attitudes and the factors influencing physician behaviour in the two countries and may be used for developing policies to improve their choices and hence to increase clinical and economic effectiveness and efficiency.